2013
DOI: 10.1152/japplphysiol.00503.2012
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic stimulation of myogenesis by glucocorticoid and IGF-I signaling

Abstract: Pansters NA, Langen RC, Wouters EF, Schols AM. Synergistic stimulation of myogenesis by glucocorticoid and IGF-I signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…This hyperplasic response, along with the apparent increases in fusion efficiency at 48hrs in DEX and MIA compared to CON, would suggest that both treatment conditions have the ability to stimulate and potentially augment myogenesis, albeit in a delayed capacity. An increased differentiation and hypertrophic capacity of C2C12's treated with DEX when co-incubated with IGF-I, has previously been reported [19]. This is thought to occur through the IGF-I-meditated translation of accumulated muscle-specific mRNA transcripts induced by DEX [19] and may in part explain the delayed, yet augmented hyperplasic phenotype observed in the DEX condition presented here.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This hyperplasic response, along with the apparent increases in fusion efficiency at 48hrs in DEX and MIA compared to CON, would suggest that both treatment conditions have the ability to stimulate and potentially augment myogenesis, albeit in a delayed capacity. An increased differentiation and hypertrophic capacity of C2C12's treated with DEX when co-incubated with IGF-I, has previously been reported [19]. This is thought to occur through the IGF-I-meditated translation of accumulated muscle-specific mRNA transcripts induced by DEX [19] and may in part explain the delayed, yet augmented hyperplasic phenotype observed in the DEX condition presented here.…”
Section: Discussionsupporting
confidence: 66%
“…An increased differentiation and hypertrophic capacity of C2C12's treated with DEX when co-incubated with IGF-I, has previously been reported [19]. This is thought to occur through the IGF-I-meditated translation of accumulated muscle-specific mRNA transcripts induced by DEX [19] and may in part explain the delayed, yet augmented hyperplasic phenotype observed in the DEX condition presented here.…”
Section: Discussionsupporting
confidence: 66%
“…We found that IGF-1 mildly increased the size of hPSC-CMs, but more importantly proved an essential factor in revealing a positive functional role for the glucocorticoid dexamethasone in this system. Synergistic effects for IGF-1 and dexamethasone have been reported in skeletal muscle and heart, with pro-differentiation and anti-atrophic effects observed ( Chrysis et al., 2011 , Pansters et al., 2013 , Schakman et al., 2008 ). Glucocorticoids also promote the structural and functional maturation of fetal mouse cardiomyocytes ( Rog-Zielinska et al., 2013 , Rog-Zielinska et al., 2015 ) but have little effect on hPSC-CMs when added alone although do affect calcium handling (G.K., C.L.M., M. Bellin, B. van Meer, L. Tertoolen, and S. Casini, unpublished data).…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, we made use of the C 2 C 12 cell culture model to investigate whether GSK-3 inhibition could prevent impaired myogenesis in response to TNF-α and the synthetic GC Dex. Impaired myogenic differentiation in response to TNF-α [80] has been reported previously, and several lines of evidence, including our own work, have demonstrated that, besides their well-described role as inducers of muscle proteolysis, GCs can also cause muscle atrophy by inhibiting several aspects of myogenesis [54,81,82]. …”
Section: Discussionmentioning
confidence: 70%
“…Repeated intranasal LPS instillation in guinea pigs resulted in an increase in plasma cortisol levels (229%, ± 48.4%), which was unaffected by SB213763-treatment (172%, ±SEM 51.2%). Previously it was demonstrated that the synthetic GCs prednisolone as well as Dex strongly impair myogenesis [54]. The addition of Dex to the culture medium during differentiation resulted in impaired C 2 C 12 myotube formation (Figure 4A).…”
Section: Resultsmentioning
confidence: 85%